Complete genome sequence and bioinformatics analysis of nine Egyptian females with clinical information from different geographic regions in Egypt - ElHefnawi, Mahmoud; Hegazy, Elsayed; Elfiky, Asmaa; Jeon, Yeonsu; Jeon, Sungwon; Bhak, Jong; Mohamed Metwally, Fateheya; Sugano, Sumio; Horiuchi, Terumi; Kazumi, Abe; Blazyte, Asta (Gene, 2021)
•We reported and analyzed the whole genomes of nine Egyptian females from different regions.•A total 12 SNPs were shared in most of subjects.•mtDNA mutation A4282G was common in all subjects.•Both mtDNA and admixture analyses showed that Egyptians sharing genetic signature and metabolic phenotypes with other Mediterranean nations. Egyptians are at a crossroad between Africa and Eurasia, providing useful genomic resources for analyzing both genetic and environmental factors for future personalized medicine. Two personal Egyptian whole genomes have been published previously by us and here nine female whole genome sequences with clinical information have been added to expand the genomic resource of Egyptian personal genomes. Here we report the analysis of whole genomes of nine Egyptian females from different regions using Illumina short-read sequencers. At 30x sequencing coverage, we identified 12 SNPs that were shared in most of the subjects associated with obesity which are concordant with their clinical diagnosis. Also, we found mtDNA mutation A4282G is common in all the samples and this is associated with chronic progressive external ophthalmoplegia (CPEO). Haplogroup and Admixture analyses revealed that most Egyptian samples are close to the other north Mediterranean, Middle Eastern, and European, respectively, possibly reflecting the into-Africa influx of human migration. In conclusion, we present whole-genome sequences of nine Egyptian females with personal clinical information that cover the diverse regions of Egypt. Although limited in sample size, the whole genomes data provides possible geno-phenotype candidate markers that are relevant to the region’s diseases.